Body size and composition of Samoan toddlers aged 18–25 months in 2019. (19th May 2021) - Oyama, Sakurako; Duckham, Rachel L.; Arslanian, Kendall J.; Kershaw, Erin E.; Strayer, Joshua A.; Fidow, Ulai T.; Naseri, Take; Hawley, Nicola L.
Abstract: Background: The " Foafoaga O le Ola (Beginning of Life)" study is a prospective birth cohort of n = 160 Samoan mother-infant dyads established in 2017–2018. A primary study aim is to explore how a missense variant at CREBRF rs373863828 impacts growth in early life, given its association with increased body size but lower risk of diabetes in adult Samoans. Here, we examine body size and composition by genotype among toddlers aged 18.7–24.5 months. Methods: Height, weight, head circumference, mid-upper-arm circumference, and abdominal circumference, as well as subscapular, triceps, iliac crest and thigh skinfold thickness were measured among 107 toddlers with known rs373863828 genotype; 42 of these toddlers completed dual-energy X-ray absorptiometry (DXA) scans from which body composition (total body less head fat mass, lean mass, bone mass, % fat mass and % fat-free mass) was estimated. Results: After controlling for sex and age, toddlers with at least one copy of the CREBRF minor allele (AA/AG) were 1.31 cm taller (SE = 0.64, p = 0.045) than toddlers with the GG genotype. Conclusion: Whether greater linear growth in early childhood could contribute to the metabolically protective effects associated with the CREBRF variant in adulthood should be explored in future studies.